1980
DOI: 10.1111/j.1943-278x.1980.tb00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Weapons: A Study of Methods of Suicide by Sex, Race, and Region

Abstract: The relationship of sex, race and region to methods of suicide are used to test the validity of two theories which attempt to explain the choice of methods among suicide victims. The two theories, lethality of intent and differential socialization with firearms, are briefly discussed. Data are collected from official death certificates in five cities during a three year period, 1969 through 1971. The findings provide little support for the lethality of intent theory. Although the differential socialization the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The results of this study are consistent with previous findings on the epidemiology of methods of suicide: for example, nonwhite suicides are more likely than white suicides to have been jumps from a height (Lester, Beck, & Bruno, 1976;Morris, Kovacs, Beck, & Wolffe, 1974;National Center for Health Statistics, 1985Swanson & Breed, 1976;Taylor & Wicks, 1980;Warshauer & Monk, 1978), and that a higher proportion of subjects with a psychiatric history (especially schizophrenia) than of other suicides had jumped (Cantor & Hill, 1990;Roy, 1982). Also as expected (Marks, 1977), women were more likely than men to have committed suicide by ingestion while men were more likely than women to have shot themselves.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are consistent with previous findings on the epidemiology of methods of suicide: for example, nonwhite suicides are more likely than white suicides to have been jumps from a height (Lester, Beck, & Bruno, 1976;Morris, Kovacs, Beck, & Wolffe, 1974;National Center for Health Statistics, 1985Swanson & Breed, 1976;Taylor & Wicks, 1980;Warshauer & Monk, 1978), and that a higher proportion of subjects with a psychiatric history (especially schizophrenia) than of other suicides had jumped (Cantor & Hill, 1990;Roy, 1982). Also as expected (Marks, 1977), women were more likely than men to have committed suicide by ingestion while men were more likely than women to have shot themselves.…”
Section: Discussionsupporting
confidence: 90%
“…Firearms are a suicide method of high (Seiden, 1977) or the highest (Card, 1974) lethality. There is increasing availability of firearms, ease of purchase, as well as a growing acceptance of firearm ownership and familiarity (Boor, 1981; Frederick, 1978; Seiden & Freitas, 1980; Taylor & Wicks, 1980). Others (Marks, 1977; Marks & Abernathy, 1974) have even suggested that firearms are the most socially acceptable method of suicide, particularly for males.…”
Section: Suicide Methods Trends and Discussionmentioning
confidence: 99%
“…In addition to racial and sexual differences in suicide method choice, most studies have compared regions of the nation or specific geographic locations, such as states or cities. These data have usually represented only a few or selected years (French & Wailes, 1980; Marks & Abernathy, 1974; Swanson & Breed, 1976; Taylor & Wicks, 1980). Boor (1981), however, surveyed national data from 1962‐1975 and noted differences in methods between whites and nonwhites.…”
mentioning
confidence: 99%
“…Studies of the general population have shown repeatedly that there are significant gender differences in methods employed for suicide, with males more likely to employ violent methods such as shooting and hanging, and females more likely to employ non‐violent methods such as poisoning with drugs or carbon monoxide (CO) (Stengel 1975; Taylor & Wicks 1980; Moscicki & Santos 1982; Rich et al . 1988; Cantor & Lewin 1990; Hassan 1995; Beautrais et al .…”
Section: Heroin Use and Methods Of Suicidementioning
confidence: 99%
“…2001). Of particular interest here, poisoning with substances such as drugs constitutes a small minority of male fatalities, but as much as a half of female deaths (Stengel 1975; Taylor & Wicks 1980; Moscicki & Santos 1982; Rich et al . 1988; Cantor & Lewin 1990; Hassan 1995; Beautrais et al .…”
Section: Heroin Use and Methods Of Suicidementioning
confidence: 99%